(untitled) (Bangladesh Heart Journal, 2022)
Background: Inferior wall acute myocardial infarction accounts for 40 to 50% of all acute STEMI. Patients of acute inferior myocardial infarction with ST depression in lateral leads often have greater incidence of triple vessel disease and proximal RCA lesion but in case of patients of acute inferior myocardial infarction with ST depression in precordial leads (leads V1 to V4), is a subject of determination whether it is associated with more sever coronary artery disease. The aim of this study is to determine the association of sum of ST depression in precordial leads with the probability of concomitant severity of coronary artery disease in patients with acute inferior STEMI. Methods: this cross sectional observational study was done at National institute of cardiovascular diseases (NICVD), Dhaka, Bangladesh. Total 90 patients of acute inferior myocardial infarction with precordial lead ST depression admitted at CCU within 12 hours of onset of chest pain were the study population. They were divided in two groups on the basis of sum of ST depression in precordial leads (Sum of ST depression d”4mm and >4mm), 36 patients in group I and 54 patients in group II. Coronary angiography was performed during the index hospitalization period. Gensini score and Reardon score were measured. Results: Overwhelming majority of the patients was male (83.3% and 90.7%) with mean age of 51.0±9.7 and 51.0±9.9 years in group I and II respectively. Smoking, hypertension and diabetes mellitus were the most frequent risk factors in both groups. Serum troponin level was significantly high in group II (6.2±2.2 vs. 13.6±17.7, p <0.05). Sum of ST depression in precordial leads was 2.84±0.66 and 7.53±3.51 in group I and group II respectively, and was statistically significant. Consideration of mean of ST depression in individual leads shows significantly higher mean in leads V2, V3 and V4 among group II patients. SVD was more frequent in group I but group II patients had higher statistically significant incidence of DVD and TVD. Gensini score (20.26±13.0 vs. 36.98±16.9) and Reardon score (4.63±2.2 vs. 6.83±2.2) was high in group II patients. Positive correlation had been depicted between summation value of ST segment depression with that of Gensini score & Reardon score (Gensini score r=0.61 and Reardon score r= 0.52). Conclusion: Involvement Triple vessel and double vessel disease was remarkably higher with increasing sum of ST segment depression in precordial leads. The severity of ST segment depression in terms of summation of ST depression in leads V1 to V4 is directly proportional to the extent and severity of coronary artery disease. Bangladesh Heart Journal 2022; 37(2): 116-121